Does government investment crowd-in or crowd-out private investment in Malaysia? - Hajian, Hoda; Mohamed, Azali (Faculty of Economics and Administration, University of Malaya, 2015)
Motivated by the concern of Malaysia’s government to increase private capital formation rate while the country has witnessed relatively low rate of private capital formation in the post-financial crisis area, this study aims to evaluate the long run relationship between private investment and government investment that is almost debt financed. Using a trivariate vector error correction model and time-series data covering last 44 years (from 1970 to 2013) this paper finds evidence of long-run complementary effect of government investment on private investment in Malaysia.